2010
DOI: 10.1111/j.1365-2990.2010.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant microRNA expression in the brains of neurodegenerative diseases: miR‐29a decreased in Alzheimer disease brains targets neurone navigator 3

Abstract: These observations suggest the hypothesis that underexpression of miR-29a affects neurodegenerative processes by enhancing neuronal NAV3 expression in AD brains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
172
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(184 citation statements)
references
References 36 publications
(44 reference statements)
7
172
3
Order By: Relevance
“…1a). On the other hand, the levels of miR-338-3p were not significantly different among the study groups, although a larger cohort is required to obtain a statistical power enough to make a definitive conclusion (23). Since miR-29a and miR-29b are located on the identical MIRN29B/ MIRN29A gene cluster on chromosome 7q32.3, their biological functions are presumably similar.…”
Section: Mir-29a Decreased In Ad Brains Targets Nav3mentioning
confidence: 88%
See 2 more Smart Citations
“…1a). On the other hand, the levels of miR-338-3p were not significantly different among the study groups, although a larger cohort is required to obtain a statistical power enough to make a definitive conclusion (23). Since miR-29a and miR-29b are located on the identical MIRN29B/ MIRN29A gene cluster on chromosome 7q32.3, their biological functions are presumably similar.…”
Section: Mir-29a Decreased In Ad Brains Targets Nav3mentioning
confidence: 88%
“…The microarray data were filtered through the following stringent criteria, that is, the detection of all signals above the threshold, the reference signal value exceeding 100, and the fold change expressed as the signal of ALS divided by the signal of the universal reference greater than 5. After filtration, we identified only three miRNAs, including miR-29a, miR-29b, and miR-338-3p, as a group of miRNAs whose expression is substantially upregulated in all three ALS brains (23).…”
Section: Mir-29a Decreased In Ad Brains Targets Nav3mentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that deregulated expression levels of certain miRNAs directly participate in the development and progression of numerous types of human cancer. In addition to its role in cancer, miR-29a has also been demonstrated to be associated with osteoblastic differentiation (15), myogenesis (16), sclerosis (17), fibrosis (18), HIV-1 replication (19), diabetes (20) and Alzheimer's disease (21). In the current study, it was identified that overexpression of miR-29a markedly suppressed the migratory and invasive capacities of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 62%
“…miR-29 family members are demonstrated to be involved in the regulation of neuron navigator 3 (NAV3) in the context of AD [84]. Studies in lung cancer and acute myelogenous leukemia have shown that the same family of miRNA directly target DNA methyltransferases DNMT3A and DNMT3B [85,86].…”
Section: Neurodegenerative Diseases Meet Cancers In a Mirna Worldmentioning
confidence: 99%